Direct Observation of Melt Convection of Silicon by X-ray Radiography - HIBIYA, Taketoshi; WATANABE, Hisao; EGUCHI, Minoru; KAKIMOTO, Koichi (JOURNAL OF THE FLOW VISUALIZATION SOCIETY OF JAPAN, 1988)
Natural and Forced convection of molten silicon during Czochralski single crystal growth was directly observed using X-ray radiography and solid tracer method. The tracer, whose density and wettability were adjusted to that of molten silicon, was newly developed. Observed flow of natural convection of molten silicon in a crucible was not only steady but also transient, and not axisymmetric but asymmetric.